\n Macroeconomic implications of natural disasters in the Caribbean - Rasmussen, Tobias N. (IMF [Washington]US, 2004)
provides a comprehensive cross-country comparison of the incidence of natural disasters. Finds that developing countries tend to suffer most from natural disasters, especially in terms of the number of persons affected and the value of the damage.